Diurnal insect identification in the Kampung Padang Plantation, Terangun district, Gayo Lues regency - Maspira Maspira; M Ali s; Ismul Huda; Abdullah Abdullah; Mimie Saputri (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Research on Identification of Diurnal Insect in Kampung Padang Plantation, Terangun Subdistrict, Gayo lues Regency was conducted in March to April 2019. This study aims (1) to find out the diurnal insect species found in Kampung Padang Plantation, Terangun Subdistrict, Gayo Lues Regency (2) to find out description of diurnal insect species found in the Kampung Padang Plantation, Terangun District, Gayo Lues Regency. (3) to determine the percentage of insect species present in the Kampung Padang Plantation, Terangun District, Gayo Lues Regency. This type of research is descriptive research. The research method used is exploring. The research location is divided into three observation stations. Data were analyzed descriptively. The results of the study (1) found 12 species of diurnal insects in the Padang village plantation Terangun sub-district Gayo Lues (2) insect species found originating from the order Lepidoptera (18 species), Coleoptera (35 species), Orthoptera (31 species), Hemiptera (25 species) species), Odoata (7 species), Diptera (18 species), and Hymenoptera (9 species) and (3) Insecta species with the highest level of attendance, originating from the Orthoptera and Coleoptera orders, while the least insect species originating from the Odonata order and Hymenoptera. The conclusion is that there are 12 species of diurnal insects consisting of 7 orders, and 12 families.